Floquet Weyl phases in a three-dimensional network model - Wang, Hailong (2018)
We study the topological properties of three-dimensional (3D) Floquet band structures, which are defined using unitary evolution matrices rather than Hamiltonians. Previously, two-dimensional band structures of this sort have been shown to exhibit anomalous topological behaviors, such as topologically nontrivial zero-Chern-number phases. We show that the band structure of a 3D network model can exhibit Weyl phases, which feature “Fermi arc” surface states like those found in Weyl semimetals. Tuning the network's coupling parameters can induce transitions between Weyl phases and various topologically distinct gapped phases. We identify a connection between the topology of the gapped phases and the topology of Weyl point trajectories in k space. The model is feasible to realize in custom electromagnetic networks, where the Weyl point trajectories can be probed by scattering parameter measurements.